A integração do direito brasileiro pelo mandado de injunção: perspectivas para o instituto no Brasil, em face da jurisprudência do Supremo Tribunal Federal - Débora Pereira Turchetti (2012)
This work aimed to identify the prospects for the writ of injunction in Brazil, taking into account the jurisprudence of the Supreme Court, and to verify the legitimacy of the Supreme Court to integrate the Brazilian legal system, with erga omnes effect, through the writ of injunction, even in case of absence of any legislation dealing on the constitutionally guaranteed right. We studied the Post-positivism, the Democratic State of Law, the new Hermeneutics, the forms of integration of the Brazilian legal system, the different doctrines on the writ of injunctions decision, the evolving jurisprudence of the Supreme Court in writ of injunction, the principle of division of Powers and the principle of access to Justice. We verify that, in the present context, the role of the judge should be reconsidered because it is his responsibility to apply the constitutional values to the case, regardless of the existence of specific legislation. We also verified that the jurisprudence of the Supreme Court in writ of injunction is shaky, because in cases concerning the right of public servant to strike was adopted the general concrete thesis, and after that, in cases concerning the right to special retirement it was adopted the individual concrete thesis. We concluded that access to Justice was completely observed only in those writs of injunction that the Supreme Court said the right in the case, using the allowed means for the integration of gaps, so those writs of injunction should be used as model for next trials. We also concluded that the fact that the Supreme Court integrates the gap in the case by deciding a writ of injunction does not injure the division of Powers, since the Supreme Court only allows the exercise of constitutionally guaranteed rights in the case. On the other hand, we concluded that the Supreme Court cant decide with erga omnes effect because it would injure the principle of division of Powers since the Constitution did not authorize the Supreme Court to develop general and abstract rules through writ of injunction.